The Effectiveness of Combining Continuous Run and Interval Training on Improving Agility, Speed, and Aerobic and Anaerobic Endurance in Futsal Athletes - Anya Maritza Asas, Tutur Jatmiko, Kunjung Ashadi, Nafisa Arif Pambudi, Fatih Hazar, Ratko Pavlovic, (Lembaga Bale Literasi, 2025)
This study aims to determine the effect of a combination of continuous run and interval training on improving speed, agility, aerobic and anaerobic endurance of male futsal athletes in Magetan Regency. The background of this study stems from the physical demands of futsal, which requires aerobic ability to maintain performance throughout the game and anaerobic ability to support repeated explosive activities. The research method used a pre-test and post-test design with the Illinois Agility Test to measure agility, a 20 m sprint to measure speed, MFT to measure aerobic endurance (VO?max), and a 300 m sprint to measure anaerobic endurance. The training program was carried out for 8 weeks with 3 training sessions per week. Data analysis used the Paired Sample t-Test at a significance level of 0.005. The research sample consisted of 20 male futsal athletes aged 16-20 years. The results showed a significant increase in agility, speed, aerobic endurance, and anaerobic endurance after the implementation of the training program. Thus, the combination of continuous run and interval training proved to be effective in improving both energy systems required for futsal performance.